2005
DOI: 10.1074/jbc.m502115200
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Endothelial Nitric-oxide Synthase Is Controlled by a Cell-specific Histone Code

Abstract: Expression of endothelial nitric-oxide synthase (eNOS) mRNA is highly restricted to the endothelial cell layer of medium to large sized arterial blood vessels. Here we assessed the chromatin environment of the eNOS gene in expressing and nonexpressing cell types. Within endothelial cells, but not a variety of nonendothelial cells, the nucleosomes that encompassed the eNOS core promoter and proximal downstream coding regions were highly enriched in acetylated histones H3 and H4 and methylated lysine 4 of histon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
189
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(198 citation statements)
references
References 80 publications
6
189
0
2
Order By: Relevance
“…To study the role of H3-K4 dimethylation on apM1 expression, we differentiated 3T3-L1 cells in the presence of MTA, a known inhibitor of AdoMet-dependent methyltransferases, that has previously been shown to inhibit H3-K4 methylation (36). Accordingly, by D5 of the differentiation process, we observed a marked decrease of global H3-K4 dimethylation in cells treated with the inhibitor.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To study the role of H3-K4 dimethylation on apM1 expression, we differentiated 3T3-L1 cells in the presence of MTA, a known inhibitor of AdoMet-dependent methyltransferases, that has previously been shown to inhibit H3-K4 methylation (36). Accordingly, by D5 of the differentiation process, we observed a marked decrease of global H3-K4 dimethylation in cells treated with the inhibitor.…”
Section: Discussionmentioning
confidence: 98%
“…Histone Modifications Spread through the apM1 Locus, Correlating with the Beginning of Gene Transcription-A host of previous studies have shown elevated levels of histone H3 hyperacetylation and K4 methylation localized to the 5Ј-proximal regions of transcriptionally active genes (2,7,36). The presence of the same modifications downstream of the transcription initiation site, on the other hand, is not as preeminent (12,37,38).…”
Section: Dimethylation Of Histone H3-k4 Is the First Modification Obsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the NOS3 promoters of all species isolated so far, including sheep, also contain binding sites for multiple additional transcription factors participating in the complex regulation of NOS3 transcription in endothelial cells in a tissue/cell, and possibly species specific manner (Chan et al, 2004). Moreover, tissue and cell-specific transcriptional regulation of NOS3 expression is controlled by methylation (Chan et al, 2004) and histone acetylation (Fish et al, 2005;Gan et al, 2005) of the NOS3 promoter. In the present study, according to the sequence information of the 5â€Č-flanking region of the sheep NOS3 gene, we hypothesized that the proximal consensus AP-1 (TGAGTCA) site positioned at the −682 to −676 upstream the ATG start codon in the sheep NOS3 gene plays an important role in the regulation of uterine artery endothelial NOS3 expression.…”
Section: Disscussionmentioning
confidence: 99%
“…Within endothelial cells, the eNOS core promoter is highly enriched in acetylated histone H3/K9 and H4/K12, and methylated H3/K4. 77 Furthermore, HDAC inhibitor trichostatin A may induce eNOS expression in non-endothelial cells, and small RNA may suppress eNOS expression by altering histone acetylation and DNA methylation in endothelial cells. 78,79 In our rat model for PPHN, the levels of eNOS mRNA and protein expression were significantly upregulated.…”
Section: Pphn and Enosmentioning
confidence: 99%